How to Define Illegal Price Manipulation - Kyle, Albert S; Viswanathan, S (American Economic Review, 2008)
The term “illegal price manipulation ” is diffi-cult to define. Current U.S. law does not explic-itly define it. The finance and economics litera-ture uses the term “manipulation ” in an impre-cise manner. This paper proposes that a trading strategy not be classified as “illegal price manip-ulation ” unless the violator’s intent is to pursue a scheme that undermines economic efficiency both by making prices less accurate as signals for efficient resource allocation and by making mar-kets less liquid for risk transfer. Since price ef-fects are market-wide, we treat the terms “price manipulation ” and “market manipulation ” as synonyms. Our definition applies equally to fi-nancial and commodities markets.